2002
DOI: 10.1046/j.1570-7458.2002.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rice lines transformed with Bacillus thuringiensis toxin genes on the brown planthopper and its predator Cyrtorhinus lividipennis

Abstract: Five transgenic rice lines, each containing an insecticidal toxin gene from Bacillus thuringiensis (Bt) under control of a different promoter, were tested for effects on two non‐target insects: the brown planthopper, Nilaparvata lugens (Stål) (Homoptera: Delphacidae), and its predator Cyrtorhinus lividipennis (Hemiptera: Miridae). Bt toxin was detected by ELISA in the honeydew of N. lugens that fed on rice lines with the CaMV 35S and actin promoters. Nilaparvata lugens produced greater volumes of acidic honeyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 27 publications
(30 reference statements)
7
66
2
Order By: Relevance
“…These results were in agreement with previous reports that Bt insecticidal protein could be detected in Bt rice-fed N. lugens (Bernal et al 2002, Chen et al 2005) and in Bt rice-fed C. medinalis (Chen et al 2009). Similarly, Bt insecticidal protein could also be transferred from Bt maize to nontarget herbivores such as the aphid Rhopalosiphum padi L. (Hemiptera: Aphididae) (Raps et al 2001) and the thrip Frankliniella tenuicornis (Uzel) (Thysanoptera: Thripidae) (Obrist et al 2005).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results were in agreement with previous reports that Bt insecticidal protein could be detected in Bt rice-fed N. lugens (Bernal et al 2002, Chen et al 2005) and in Bt rice-fed C. medinalis (Chen et al 2009). Similarly, Bt insecticidal protein could also be transferred from Bt maize to nontarget herbivores such as the aphid Rhopalosiphum padi L. (Hemiptera: Aphididae) (Raps et al 2001) and the thrip Frankliniella tenuicornis (Uzel) (Thysanoptera: Thripidae) (Obrist et al 2005).…”
Section: Discussionsupporting
confidence: 94%
“…For example, none of the development and reproduction parameters were differed when measured in the brown planthopper, N. lugens, and the white-backed planthopper, S. furcifera reared on Bt rice MSA and MSB expressing a fusion protein of Cry1Ab/CpTI and non-Bt rice (Fu et al 2003). Similarly, there was no difference in any of the Þve Þtness parameters (survival to the adult stage, male and female weight, and male and female developmental time) between N. lugens reared on Bt rice and control lines (Bernal et al 2002). Tan et al (2006) also reported that Bt rice B1 and B6 signiÞcantly affect neither oviposition behavior nor fecundity of the white-backed planthopper.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, the relative abundance of the four natural enemy arthropods within the predator guild was similar in the non-transgenic and transgenic Bt rice fields. Therefore, although the densities of C. medinalis were significantly lower in the transgenic Bt rice, the lower predator populations did not result from ap- plication of Bt rice, a similar result to previous reports [10,18,31]. In most cases (75%), the population dynamics of C. medinalis adults were not affected by rice line, rice line×sam-pling date, rice line×year, rice line×sampling date×year, and no consistent effects of rice line, rice line×sampling date, rice line×year, rice line×sampling date×year on the population dynamics of C. medinalis adults were observed at different experiment sites.…”
Section: Discussionsupporting
confidence: 91%
“…Each crop genotype interacts differently with gene promoters and the products they regulate, making it difficult to generalize where the transgenic toxins will ultimately reside in the plant. For instance, Cry toxins are not found in the phloem tissues of some maize events ), but these toxins are detectable in the phloem of some rice, oilseed rape, and other maize events (Raps et al, 2001;Bernal et al, 2002a;Burgio et al, 2007). The end result is that numerous factors influence whether non-prey foods will be contaminated with insecticides from GM crops.…”
Section: Part I Pathways Through Which Natural Enemies May Be Affectmentioning
confidence: 99%